The Concept of Moral Education From The Perspective of Shaykh Sa'id Bin' Ali Al Qahatani - Muhammad Nurul Fikri; Amin Fauzi (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2026)
This research is conducted with the aim of deeply examining the concept of moral education proposed by Sheik Sa'id bin 'Ali Al-Qahtani and its significance for the development of Islamic education in the modern era, considering the degradation of moral-spiritual behavior among the younger generation, which seems to be increasingly driven by the influence of globalization and the advancement of digital technology. The methodology of this research employs a qualitative approach using library research, conducted thru a systematic textual analysis of various scientific works authored by Al-Qahtani as well as various literature related to contemporary Islamic education. Data collection was obtained from various primary sources such as books, reputable scientific journal articles, academic papers, Quranic exegesis, authentic hadiths, as well as various religious treatises that have conceptual correlations with the theme of moral education. Data analysis techniques are carried out thru several structured stages, including data reduction, thematic categorization, content interpretation, and descriptive-analytical conclusion drawing. This research provides an intellectual contribution to enriching the realm of Islamic education by integrating spiritual values with character formation based on ethics. The implications that can be drawn from this research emphasize the need for cross-sector synergy between families, educational institutions, and the broader community in the comprehensive and holistic implementation of moral education. For the development of future research, it is recommended to further examine the practical implementation of Al-Qahtani's moral education concept in various formal and non-formal educational institutions more intensively and in-depth.